Yes, the term is always one level up.

General term: 10Cr (x^10-r) (-1/x)^r = 10Cr (-1)^r (x)^10-2r

What is the middle term? The 6th term, (as (r=1)th term), the 6th term’s r =5.

10C5 (x)^5 (-1/x)^5 = -252

Step1: To expand the first two and last two terms and set the middle ones as (…). Hint: to help you to find the pattern first.

Step2: find the general term

Step3: Simplify general term

Step4: set the power of x = 0, get the r

Step5: sub r=3 into constant term, {Original: 9Cr (2^9-r) (-3)^r (x^9-3r) }; But we want constant term, so we set x power to 0, and sub r=3, {New: 9C3 (2^6) (-3)^3 x^0}, equals to =-145152

# Ex1 Q2c

2c) The general term: 13Cr · (t)^(13-r) · (3/t)^r = 13Cr · (t)^(13-r) · (3/t)^r = 13Cr · 3^r · t^(13-2r)